Maintenance Optimization of Repairable Systems Under a Diffusion Approximation Scheme - Chetouani, Hassan; Limnios, Nikolaos; Shen, Jingyuan (Methodology and computing in applied probability, 2025)
In this paper we study maintenance optimization of the repairman problem. The temporal description of this problem is given by a Markov process of birth-and-death type. The maintenance consideration of this problem, considering all states, is difficult. Based on a diffusion approximation we formulate the maintenance policy and then we optimize it in a much easier way. The associated cost includes cost for lack of repairmen, cost for busy repairmen, cost of excess of spare items, and cost of lack of spare items. Based on the limit process obtained by the diffusion approximation of the original Markov process, we optimize the maintenance by minimizing the cost function. A numerical example is given with more than one hundred states.